Tourism-Led Economic Growth in Coastal Areas: A Qualitative Study of Marine Economies - Santoso, Rudi (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2025)
Objective: This research aims to explore the strategic role of the marine tourism sector in encouraging economic growth in coastal areas, with case studies on several coastal areas. Design/Methods/Approach: Departing from the tourism-led growth paradigm, this study uses a descriptive qualitative approach through in-depth interviews, participatory observations, and documentation studies of key actors in the marine economic ecosystem, including business actors, local governments, and local communities Findings: The findings of the study show that marine tourism has become a catalyst for economic diversification, the creation of new jobs, and the increase of economic participation of local communities, especially in the informal sector, such as culinary, lodging, and tourism services. The study also identified good practices from community-based tourism models that successfully integrate economic and conservation aspects through active community participation. Originality/Value: This research contributes to the development of inclusive marine tourism theory and enriches the literature on economic growth based on local potential. The results of the research are expected to be a policy reference for inclusive, competitive, and sustainable coastal economic development. Practical/Policy implication: Strategic recommendations are provided to stakeholders to strengthen governance, community empowerment, investment partnerships, and cross-sectoral policy integration.